Christoph Hein's Horns Ende. Historical Revisionism: A Process of Renewal - Heinz Bulmahn (Studies in 20th & 21st Century Literature, 1991)
In light of recent developments, the historical record of the German Democratic Republic will be closely reexamined as the two Germanies merge into one country. Christoph Hein's novel Horns Ende undoubtedly will play a role in the debate about the GDR past, because it is a clear repudiation of official historical mythmaking. The novel examines in detail the political and social fiber of a small town in the GDR during the fifties. Horn returns to the town some thirty years after his death, and entices the townspeople to recount their lives during the early years of the socialist republic. These recollections initiate a dialogue between author, reader and the townspeople. The outcome of these exchanges is a skillful dissection of the effects of Stalinism on ordinary citizens, and it revises perceptions of a period in GDR history that officially had been touted as politically and socially harmonious. Hein challenges the reader to reconstruct a historical record that more closely reflects the experiences of ordinary people, and in doing so he exposes past official historical mythmaking. He is convinced that a society's survival is dependent upon the accuracy of its history; historical revision therefore must not be left to those in power.
Keywords: German Democratic Republic; GDR; two Germanies; Germanies; Christoph Hein; Horns Ende; past; mythmaking; political; social; fifties; 50s; death; socialist republic; dialogue; author; reader; townspeople; Stalinism; reconstruct; history; perspective